Unraveling epigastric pain: A case report - Oliveira, Ana Correia de (2016)
Introduction: Epigastric pain is frequently associated with gastrointestinal disease. However, when faced with a patient complaining of epigastric pain it is important to obtain a careful history and perform a physical examination because this may also be associated with other diseases. Case Description: We present the story of a 41 year-old man with a history of smoking, dyslipidemia, hypertension and obesity. His father died at age 46 from an acute myocardial infarction. In July 2014 he came to a private clinic complaining of epigastric pain. Following a brief history and physical examination, he received analgesia and gastric mucosal protection with improvement in his symptoms. One month later, he experienced a similar episode of pain, without recourse to medical assistance. In September 2014, came to his family doctor and requested further examinations, including gastroscopy and colonoscopy. The patient also reported that during episodes of epigastric pain he had also experienced a sense of left upper limb numbness. The doctor ordered additional tests, including biochemical analyses, an abdominal ultrasound, an electrocardiogram (ECG), and a stress test. The patient was then referred for an urgent consultation with a cardiologist and coronary artery bypass surgery was performed for triple vessel disease. Discussion: The incidence of heart disease is increasing along with the prevalence of risk factors for cardiovascular disease. This patient had several risk factors that might suggest atypical ischemic pain as the cause of his epigastric pain. Physicians are aware of the most common causes of symptoms reported by the patient but must also consider atypical presentations of less common diagnoses.